PHYTO-BENEFICIAL EFFECTS AND MOLECULAR CHARACTERISATION OF RHIZOBACTERIA OF MAIZE (ZEA MAYSL.) (2013)
Maize is a crop that harbours diverse groups of rhizosphere microorganisms, among which are beneficial rhizobacteria known to enhance maize growth. However, there is limited information on their use in southwestern Nigeria due to challenges in selection and identification of isolates. Therefore, a good understanding of these beneficial isolates is needed. Hence, the objective of this study was to determine the phyto-beneficial effects of rhizobacteria with a view to enhancing maize growth in southwestern Nigeria and to characterise the rhizobacteria. Four locations were randomly selected in each of the five ecological zones (Guinea savannah, Derived savannah, Lowland rainforest, Fresh water swampy forest and Mangrove forest) in southwestern Nigeria. For each location,rhizosphere soil samples were collected from five randomly selected maize plants in five different farm sites. Overall, 25rhizosphere soil samples were collected and pooled together to form a composite soil for each location. Bacteria load and growth promoting characteristics such as production of indole-3-acetic acid, chitinase enzyme activity, phosphate solubilization and effect on maize seed germinationwere assessed using standard methods. Phyto-beneficial effect of isolates on maize was carried out in the screenhouse using complete randomized design with three replications. Parameters assessed included disease expression, bacteria load, soil pH, plant height, stem girth, Number of Leaves (NL), leaf area, Shoot Dry Matter (SDM) and nutrient uptake. The best growth promoting rhizobacteria were selected and characterised using 16S rDNA. Total genomic DNA was extracted by quick prep method, from which the 16SrDNA gene was amplified and sequenced. The sequences obtained were compared with those of GenBank reference strains for similarity. Data were analysed using ANOVA at p = 0.05 and Pearson correlation. The bacteria load (11.5 x 106 191.0 x 106cfu/g of soil) significantly varied with respect to each location across the ecological zones. A total of 445 bacteria were isolated, 10.8% of them produced indole-3-acetic acid, 7.0% showed high chitinase enzyme activity, 6.7% solubilized phosphate, 9.3% enhanced maize seed germination and 66.2% did not show any growth promoting characteristics. Nineteen isolates exhibitedphyto-beneficial effects on maize plant with evidence of no disease symptoms. Out of these, 12 consistently performed better as phyto-beneficial rhizobacteria. Maize plant height, stem girth, NL, leaf area, SDM and nutrient uptake were significantly enhanced by the 12 rhizobacteria. Relationship (r = 0.510) existed between soil pH andbacteria load. The sequences of beneficialrhizobacteriaisolates showed 90.099.0% similarity to those of GenBank reference strains. Phylla taxonomy group showed that, Proteobacteria dominated (41.6%), followed by Bacteroidetes (33.3%) and then Firmicutes (25.1%). The 16S rDNA revealed isolates identity as Myroidesodoratus(4 strains),Enterobacterpyrinus, Enterobacterradicincitans, Bacillus aeolius, Bacillus niacini, Lysinibacillusboronitolerans, Citrobacterfameri, Stenotrophomonasmaltophilia and Azomonasmacrocytogenes. Different species of phyto-beneficial rhizobacteria inhabiting rhizosphere of maize plants in southwestern Nigeria were identified using 16S rDNA molecular technique. The phyto-beneficial rhizobacteria enhanced maize growth and nutrient uptake, thus, could be employed in maize farming.